2019
DOI: 10.1136/bmjopen-2018-027953
|View full text |Cite
|
Sign up to set email alerts
|

Cochrane systematic review and meta-analysis of botulinum toxin for the prevention of migraine

Abstract: ObjectivesTo assess the effects of botulinum toxin for prevention of migraine in adults.DesignSystematic review and meta-analysis.Data sourcesCENTRAL, MEDLINE, Embase and trial registries.Eligibility criteriaWe included randomised controlled trials (RCTs) of botulinum toxin compared with placebo, active treatment or clinically relevant different dose for adults with chronic or episodic migraine, with or without the additional diagnosis of medication overuse headache.Data extraction and synthesisCochrane method… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
73
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 89 publications
(82 citation statements)
references
References 39 publications
8
73
0
1
Order By: Relevance
“…Despite this, our findings at 12 weeks are similar to those of the recent metaanalysis by (Bruloy et al, 2019), wherein a mean difference in the change of migraine frequency of -0.23 (95 percent CI, -0.47 to 0.02; P = 0.08) was reported. Furthermore, our overall results are consistent with those of Herd et al (Herd et al, 2019) regarding changes in headache episodes per month. Intramuscular BTX-A for chronic migraine prevention is based on a previous study of its effectiveness in transient muscle relaxation (Burstein et al, 2014;Gooriah and Ahmed, 2015;Simpson, 2004).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Despite this, our findings at 12 weeks are similar to those of the recent metaanalysis by (Bruloy et al, 2019), wherein a mean difference in the change of migraine frequency of -0.23 (95 percent CI, -0.47 to 0.02; P = 0.08) was reported. Furthermore, our overall results are consistent with those of Herd et al (Herd et al, 2019) regarding changes in headache episodes per month. Intramuscular BTX-A for chronic migraine prevention is based on a previous study of its effectiveness in transient muscle relaxation (Burstein et al, 2014;Gooriah and Ahmed, 2015;Simpson, 2004).…”
Section: Discussionsupporting
confidence: 93%
“…These differences remained significant when considering specific complications, including headache, injection-site pain, musculoskeletal stiffness, myalgia, neck pain, paresthesias, muscle weakness, palpebral fissure, and blepharoptosis. Related studies (Herd et al, 2019) have also reported that BTX-A increases treatment-related AEs, but event types were reportedly mild and short-lived.…”
Section: Discussionmentioning
confidence: 89%
“…The optimal management of CM associated with medication overuse is in fact controversial. Medication overuse is not a contraindication to BT-A treatment for CM and does not preclude its effectiveness [39,41]. However, detoxication prior to BT-A initiation may per se determine reversion of CM and may improve the efficacy [42].…”
Section: Discussionmentioning
confidence: 99%
“…Several SRs examined the e cacy of acupuncture [11,42], BoNT-A [5,43], or topiramate [10,44,45] in migraine prophylaxis. Most of the SRs focused on the e cacy of the 3 treatments in episodic migraine; and none of them has compared the 3 treatments by combining both direct and indirect evidence.…”
Section: Discussionmentioning
confidence: 99%
“…As indicated by several systematic reviews and randomized controlled trials (RCTs), BoNT-A reduced the number of headache days and global pain intensity in patients with chronic migraine [3,4]. One systematic review indicated that BoNT-A had a relatively higher acceptance rate than other prophylactic agents [5], but the hypothesis was not statistically tested because of the lack of head-to-head comparisons. The e cacy of topiramate in the preventive treatment of chronic migraine was tested in several RCTs and meta-analyses [6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%